The COVID-19 pandemic impact upon housing brokers' workflow and their clients' attitude: Real estate market in Krakow - Bartłomiej Marona; Mateusz Tomal (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to assess the impact of COVID-19 pandemic upon the workflow of real estate brokers and their clients' attitude as exemplified by the real estate market in Krakow. Research Design & Methods: For the purpose of assessing the impact of COVID-19 pandemic upon the aspects of the real estate market under consideration, a survey questionnaire with open-ended questions was distributed amongst all the real estate brokers associated in the Malopolska Real Estate Brokers Association. Findings: The findings indicate that the COVID-19 pandemic has had a considerable impact upon the workflow of real estate brokers and their clients' attitude. The real estate brokers began to render online services to a greater extent, thus they intensified the use of digital technologies in running their businesses. On the other hand, their clients like landlords in numerous cases changed their strategies, i.e. from short-term rental into the long-term one. In turn, tenants began to demand lower rents and higher standards of apartments. Implications & Recommendations: The conducted studies have made it plausible to state that the COVID-19 pandemic has had a significant impact upon the real estate market. However, it bears noting that we do not conclude to what extent those changes are permanent, therefore the need for further studies.
Keywords: D22; D23; H12; R00; 330; housing market; COVID-19; SARS-CoV-2; realtor; housing preferences